2009
DOI: 10.1002/elps.200800386
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional phosphate‐affinity gel electrophoresis for the analysis of phosphoprotein isotypes

Abstract: Herein, we describe three kinds of 2-DE using phosphate-affinity PAGE for the analysis of phosphoprotein isotypes. The first dimension is a urea-PAGE, IEF/NEPHGE, or SDS-PAGE, which are widely used. The second dimension is a phosphate-affinity SDS-PAGE using a phosphate-binding tag molecule, Phos-tag (Mn(2+)-Phos-tag SDS-PAGE). The first 2-D procedure coupling urea-PAGE and Mn(2+)-Phos-tag SDS-PAGE was applied to the separation of beta-casein phosphoisotypes. A typical protein sample containing multiple phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Because this system is compatible with the equipment and reagents used for the conventional SDS-PAGE followed by general Western blotting analysis with a specific antibody against a certain target [27][28][29][30][31], many researchers have used it in the intervening years and have reported valuable findings related to protein phosphorylation modifications not only in the field of basic life sciences but also in the field of clinical medicine.…”
Section: Overviewmentioning
confidence: 99%
“…Because this system is compatible with the equipment and reagents used for the conventional SDS-PAGE followed by general Western blotting analysis with a specific antibody against a certain target [27][28][29][30][31], many researchers have used it in the intervening years and have reported valuable findings related to protein phosphorylation modifications not only in the field of basic life sciences but also in the field of clinical medicine.…”
Section: Overviewmentioning
confidence: 99%
“…Consistent with the notion that many proteins are multiply phosphorylated inside the cell, a ladder of clearly distinguishable bands is often observed using Phos-Tag electrophoresis. Though several studies have used Phos-Tag technologies either to profile the phosphorylation status of select substrates (Kinoshita et al, 2009; Aguilar et al, 2011; Kinoshita-Kikuta et al, 2012) or to validate substrates identified by other methods (Mukai et al, 2008; Deswal et al, 2010; Mok et al, 2010; Huang et al, 2014; Yip et al, 2014), to date Phos-Tag electrophoresis has not been applied to large-scale proteomic analyses. It will be interesting to compare the results of such studies with those obtained using standard 1D SDS-PAGE—such as the one conducted by Matsuda et al in S. pombe (Shirai et al, 2008)—as well as with those that utilize 2D-PAGE, as described below.…”
Section: Substrate Selection: Identifying the Cellular Targets Of Promentioning
confidence: 99%
“…Phos-tag SDS-PAGE is a recently developed method that is capable of separating phosphorylated proteins on SDS-PAGE (12) and has been used to show phosphorylation of proteins (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). When this technique was initially reported, Kinoshita et al (12) predicted its use in quantitative estimation of in vivo phosphorylation.…”
Section: Phosphorylation Of P35 Analyzed By Phos-tag Sds-pagementioning
confidence: 99%
“…Because the migration of the phosphorylated proteins is greatly delayed compared with migration in Laemmli SDS-PAGE, it is easy to identify the phosphorylated proteins from observed positions on blots. In the past 3 years, this method has been used to detect phosphorylation states for many proteins such as ERK1/2, cdc37, myosin light chain, eIF2␣, protein kinase D, ␤-casein, SIRT7, and dysbindin-1 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%